'Learning to live with OCD is a little mantra I often repeat': Understanding the lived experience of obsessive‐compulsive disorder (OCD) in the contemporary therapeutic context. (12th October 2012) - Murphy, Helen; Perera‐Delcourt, Ramesh
<x xml:space="preserve">Abstract</x> Objectives While there has been an abundance of quantitative studies that examine the clinical features and treatment modalities of obsessive‐compulsive disorder (OCD), only a few qualitative research studies examining the experience of OCD have been documented. Our objectives were to explore and understand psychosocial aspects of OCD and to provide qualitative accounts of the condition and its treatment rather than concentrating on its psychopathology. We also wanted to locate the role cognitive behavioural therapy (CBT) played in the condition for our participants. Design Data for the study came from a series of nine semi‐structured interviews carried out with individuals who self‐identified as having OCD. Participants were recruited through two leading UK‐based OCD charities. Methods We used interpretative phenomenological analysis (IPA) to analyse the accounts and participants gave feedback as to the validity of the themes in early stages of analysis. Results We report two superordinate themes – Having OCD (with subordinate themes 'wanting to be normal and fit it', 'failing at life' and 'loving and hating OCD') and The Impact of Therapy (with subordinate themes of 'wanting therapy', 'finding the roots' and 'a better self'). Conclusions Having OCD as a condition meant that individuals experienced a sense of overwhelming personal failure matched against age appropriate life cycle goals. This crisis of the self was bolstered by public and self‐stigma about the condition. While clinical diagnosis and therapeutic interventions were significant, participants reported dialectical tensions experienced with OCD, pointing to the complexity of psychological functioning in the condition. Practitioner Points Participants experienced a 'deficit identity' as a result of OCD, impacting on self‐esteem and self‐confidence. While participants valued a medical diagnosis of OCD, there was ambivalence in 'letting go' of OCD behaviours. Some participants experienced CBT as an intervention which prevented them telling their OCD story. Participants valued the therapeutic relationship, especially in understanding and talking through the origins of OCD.